PENGARUH DIGITAL LIBRARY TERHADAP MINAT BACA MAHASISWA - kholili zailani; Muhammad Husni Hamdani; Evi Fatimatur Rusydiyah (Akademika, 2022)
The Digital Library (DIGILIB) or Digital Library has a short but tumultuous and explosive history. Some early visionaries, such as Licklider 1965, had the idea that "the libraries of tomorrow will be highly innovative and differentiated in structure, processing, and access through heavy technological applications. This study uses a quantitative approach to the type of correlation research. Knowledgeable quantitative research using data in the form of numbers as a tool to find information about what we want to know. This study aims to determine the effect of digital libraries on students' reading interest at Sunan Ampel State Islamic University. The sample in this study were students of the Islamic religious education master's degree class B, totaling 13 students. Based on the results of the research that has been described, decision making in a simple linear regression test, based on the significance value of the coefficient table, a significance value of 0.000 <0.05 is obtained, so it can be concluded that Digital Library (X) has an effect on Student Reading Interest (Y). and it is known that t count is 3.038 > t table 2.20099, so it can be concluded that the use of digital libraries has an effect on students' reading interest (Ha).Keywords: Digital Library, Reading Interest